2013
DOI: 10.1165/rcmb.2012-0060oc
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Suppression of IL-13 by a Vaccine Attenuates Airway Inflammation and Remodeling in Mice

Abstract: We previously reported that a recombinant IL-13 peptide-based virus-like particle vaccine significantly suppressed murine acute airway allergic inflammatory responses. The impact of this strategy on the development of chronic airway inflammation and remodeling has not been investigated. We evaluated whether the vaccine-mediated sustained suppression of IL-13 attenuates features of chronic airway inflammation and remodeling in mice repeatedly challenged with allergen. BALB/c mice received two intraperitoneal se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 40 publications
0
31
0
2
Order By: Relevance
“…As we have described (40), under inhaled anaesthesia (isoflurane) 8-wk-old Balb/c mice were exposed intranasally to 35 l of saline containing purified house dust mite (HDM) whole body extract (2.5 g/l HDM-protein extract in saline) (Greer Laboratories) for 5 consecutive days over 2 consecutive wk initially and followed by HDM exposure three times a week on alternative days for an additional 3 wk. All studies were performed using animals and protocols approved by the Animal Ethics Committee of the University of Manitoba.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have described (40), under inhaled anaesthesia (isoflurane) 8-wk-old Balb/c mice were exposed intranasally to 35 l of saline containing purified house dust mite (HDM) whole body extract (2.5 g/l HDM-protein extract in saline) (Greer Laboratories) for 5 consecutive days over 2 consecutive wk initially and followed by HDM exposure three times a week on alternative days for an additional 3 wk. All studies were performed using animals and protocols approved by the Animal Ethics Committee of the University of Manitoba.…”
Section: Methodsmentioning
confidence: 99%
“…All subjects gave informed consent and subjects were grouped according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) classification using predicted forced expiratory volume in 1 s (FEV 1) and FEV1 to forced vital capacity (FVC) ratio (Table 1). Murine lungs were fixed in 4% formalin and processed as previously described (40). For histology, segmental sections were deparaffinised in xylene and rehydrated in graded solutions of ethanol and subjected to epitope unmasking in citrate buffer (0.1 M citric acid and 0.1 M sodium citrate, pH 6.0) for 20 min at 90°C followed by cooling at room temperature for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…23 Several peptide epitopes from inflammatory cytokines which are key mediators in pathogenesis of asthma or inflammatory bowel diseases have been successfully presented onto the surface of HBcAg VLPs, and immunization with these VLPs ameliorated significantly the development of diseases manifests in animal models. 13,[24][25][26] However, linear epitopes may be not powerful enough to elicit efficient neutralizing antibodies (our unpublished data). Moreover, based on our previous experience, the assembling ability of HBcAg might be destroyed even if a short peptide is inserted, and sometimes even an amino acid alteration within the successfully inserted peptide would hamper the VLPs assembly (our unpublished data).…”
Section: Discussionmentioning
confidence: 95%
“…It has been proven that as a vaccine carrier, HBcAg can be extremely effective in helping self antigens evade B-cell tolerance, even without the use of conventional adjuvants. 16,17 The highly immunogenic features of HBcAg are attributed to the following characteristics: the structure of its nanoparticle, which facilitates their uptake by antigen-presenting cells (APCs), 21 their ability to activate naive B-cells to function as APCs with 10 5 -fold higher efficiency than typical dendritic cell and macrophage interactions, 14 the unique highly ordered and repetitive arrays of inserted self-peptides (up to 240 copies for each VLP), 13,22 and the presence of welldefined T-helper cell epitopes in the primary sequence. 14,15 Furthermore, it was reported that nucleic acids packed into VLPs also significantly contribute to the immunogenicity of HBcAg VLPs as well as induced immune response types.…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, HBcAg VLPs presenting self molecules and peptides could evade immune tolerance, induce specific autoantibodies, and successfully intervene with the pathological effects of dysfunctional target molecules in disease models. 16,17 However, whether HBcAg VLPs are likely to be used as a therapeutic vaccine carrier and whether they facilitate antigen-specific cellular immune responses have not yet been well identified.…”
Section: Chu Et Almentioning
confidence: 99%